Pengaruh Adversity Quotient Pada Komitmen Organisasi - Putri, Nadya Okta Eka (Peneliti.net, 2024)
One of the various factors influencing a company's success in achieving its goals is the level of employee commitment to the company. This research was conducted by collecting data through a survey distributing questionnaires to 92 working respondents. The analysis method employed was quantitative, utilizing the Statistical Product and Service Solutions (SPSS) version 22 software for Windows. Data were gathered using Likert scale questionnaires, with samples taken through non-probability sampling using purposive sampling technique. Analysis was performed using simple regression to examine the relationship between organizational commitment (Y) and adversity quotient (X). The research findings indicate a significant relationship between adversity quotient and organizational commitment, with a significance value of 0.004 (<0.05); (F=8.644; p<0.05). With a coefficient of determination of 0.088, it can be concluded that adversity quotient influences organizational commitment by 9%, while other factors outside the scope of the study affect 91% of the organizational commitment variable